EFEKTIVITAS BIMBINGAN KLASIKAL DENGAN TEKNIK LINGKARAN (ROUND) UNTUK MENGURANGI KECEMASAN BERBICARA DI DEPAN KELAS - Yuli Diniawati; Agus Wibowo; Mudaim (Universitas Muhammadiyah Metro, 2024)
The expected research and development objectives in “this study are to reduce the anxiety of speaking in front of the class of class XI learners at SMK Muhammadiyah 1 Metro” and testing the effectiveness of classical guidance services with the circle technique (round) that researchers develop. The type of research is experimentation, which is research using quantitative data. Quantitative data obtained based on the results of the student response assessment score and anxiety questionnaires speaking in front of the class that researchers give to learners.This development research was conducted using classical guidance research method with circle technique (round) using game media so that students When carrying out services do not feel bored. The results of the research conducted are : 1) The effectiveness of classical guidance services with the circle (round) technique to reduce anxiety of speaking in front of a class of learners class XI at SMK Muhammadiyah 1 Metro who managend to get results with the category of “high and medium” which can be seen as follows : a) the average pretest score results get a score 0f 77,08 with the “high” category, b) the average postest score gets a score of 63,08 with the “low” category, c) The results of the hypothesis also show that the results of the thitung large than of sigtificans 0,10 thus H0 rejected and accepted. This means that in this study there is a significant influence between variables independent of dependent variables so that there is an influence on reducing anxiety of speaking in front of the class on students at SMK Muhammadiyah 1 Metro well.